The Secrets of Happiness at Work. A Case Study of Private Healthcare Providers in Dubai - GEBBA, Tarek Roshdy; KHAN, Bushra; KHAN, Naseer (Journal of Advanced Research in Management, 2019)
The role of employee happiness is important for healthcare organizations and is central to efficient management practice. The purpose of this paper is to explore the secrets of happiness at work in the private healthcare sector of Dubai. More specifically, it examines the factors influencing the happiness of employees working in the private healthcare organizations in Dubai. This study uses a collection of research methods, including a comprehensive revision of all relevant publications and documents, interviews and a questionnaire survey. The questionnaire was distributed to six hundred fifty employees working in 27 large, medium and small private healthcare organizations in Dubai. A total of 443 questionnaires were returned, giving us a final response rate of 68%. The results of this study provide insights into the factors influencing happiness at work in Dubai’s private healthcare organizations. These factors as ranked by respondents, including effective working relationships with colleagues, company’s financial stability, normal work-life balance, attractive salary, interesting job, recognition, good relationships with superiors, job security, autonomy, company values, appreciation for work and learning and career development opportunities. Furthermore, results revealed that high levels of healthcare employee happiness help to empower and persuade colleagues, especially when they are faced by challenges while dealing with critical health care issues of the patients.